Clinical experience of volumetric‐modulated flattening filter free stereotactic body radiation therapy of lesions in the lung with deep inspiration breath‐hold. Issue 9 (22nd July 2022) - Mørkeset, Siri T.; Lervåg, Christoffer; Lund, Jo‐Åsmund; Jensen, Christer
Abstract: This clinical study aimed to evaluate lung cancer patients' ability to perform deep inspiration breath‐hold (DIBH) during CT simulation and throughout the treatment course of stereotactic body radiation therapy (SBRT). In addition, target sizes, organ at risk (OAR) sizes, and doses to the respective volumes in filter‐free volumetric‐modulated arc therapy plans performed under free‐breathing (FB) and DIBH conditions were evaluated. Twenty‐one patients with peripheral lesions were included, of which 13 were eligible for SBRT. All patients underwent training for breath‐hold during CT, and if they complied with the requirements, two CT scans were obtained: CT scan in DIBH and a four‐dimensional CT scan in FB. The treatment plans in FB and DIBH were generated, and the dose parameters and volume sizes were compared. The endpoints for evaluation were patient compliance, target dose coverage, and doses to the OARs. This clinical study showed high patient DIBH compliance during both CT simulation and treatment for patients with lung cancer. A significant reduction in target volumes was achieved with SBRT in DIBH, in addition to significantly decreased doses to the heart, chest wall, and lungs. DIBH in SBRT of lung lesions is feasible, and a routine to manage intra‐fractional deviation should be established upon implementation.